Agricultural Teachers’ Attitude towards Teaching Profession - Renu Balakrishnan , Premlata Singh , Eldho Varghese , Ashish Santosh Murai (Indian Journal of Extension Education, 2018)
Attitude is a feeling of like, dislike, attraction, repulsion, interest or apathy towards other persons, objects or ideas. Teachers have a huge role to play in realizing future agricultural revolutions by guiding and mentoring agricultural higher education students. Therefore, it is very much necessary to know that how the agricultural teachers feel about their profession and what the reasons are behind having such feelings. The study was undertaken in four reputed Agricultural Universities of India: ICAR- IARI, New Delhi; ICAR- NDRI, Karnal; TNAU, Coimbatore and UAS, Bangalore constituting a total sample size of 180 agricultural teachers. The study revealed that agricultural teachers in these universities had a positive attitude towards teaching.